(untitled) (Revista Brasileira Multidisciplinar, 2021)
Different management strategies and products can be adopted for weed control and seed treatment. This study evaluated the effect of metsulfuron-methyl application on the establishment of soybean (Glycine max Merril. L) at two herbicide application times and in response to micronutrient and amino acid seed treatment. The soybean seeds, cultivar Nidera 5909, were submitted to the following treatments: control (without treatment); amino acid; micronutrient 1 (a product containing amino acids from seaweed, cobalt, and molybdenum) and micronutrient 2 (a product containing amino acids from seaweed). The sowing periods occurred 15 days after the herbicide application or immediately after its application. We evaluated the emergence of seedlings at seven and 14 days after sowing (DAS), and the dry matters of roots and shoots at 14 and 21 DAS. The metsulfuron-methyl affected the seedling emergence at seven days after the sowing in seed treated with micronutrient 1 immediately after the herbicide application. At 21 DAS, a reduction in the dry mass of seedling roots was observed, which sowing occurred immediately after the application of the herbicide. The application of metsulfuron-methyl at sowing may damage the establishment and performance of soybean seedlings. Therefore, it is important to carry out sowing respecting the period of carryover effects from the herbicide, in order to prevent phytotoxicity symptoms to the soybean crop.